Evolution of DNA methylome from precancerous lesions to invasive lung adenocarcinomas - Hu, Xin; Estecio, Marcos R.; Chen, Runzhe; Reuben, Alexandre; Wang, Linghua; Fujimoto, Junya; Carrot-Zhang, Jian; McGranahan, Nicholas; Ying, Lisha; Fukuoka, Junya; Chow, Chi-Wan; Pham, Hoa H. N.; et al. (Nature communications, 2021)
The evolution of DNA methylome and methylation intra-tumor heterogeneity (ITH) during early carcinogenesis of lung adenocarcinoma has not been systematically studied. We perform reduced representation bisulfite sequencing of invasive lung adenocarcinoma and its precursors, atypical adenomatous hyperplasia, adenocarcinoma in situ and minimally invasive adenocarcinoma. We observe gradual increase of methylation aberrations and significantly higher level of methylation ITH in later-stage lesions. The phylogenetic patterns inferred from methylation aberrations resemble those based on somatic mutations suggesting parallel methylation and genetic evolution. De-convolution reveal higher ratio of T regulatory cells (Tregs) versus CD8 + T cells in later-stage diseases, implying progressive immunosuppression with neoplastic progression. Furthermore, increased global hypomethylation is associated with higher mutation burden, copy number variation burden and AI burden as well as higher Treg/CD8 ratio, highlighting the potential impact of methylation on chromosomal instability, mutagenesis and tumor immune microenvironment during early carcinogenesis of lung adenocarcinomas. It is known that invasive lung adenocarcinomas evolve from pre-cancerous dysplastic lesions. In this study, the authors show that evolution of pre-cancerous lesions is accompanied by DNA methylation alterations, and that global hypomethylation correlates with immune infiltration, mutational burden and copy number alterations.